A near-infrared fluorescent long-chain fatty acid toward optical imaging of cardiac metabolism in living mice. Issue 19 (3rd September 2022) - Swamy, Mahadeva M. M.; Zubir, Mohamad Zarif Mohd; Mutmainah,; Tsuboi, Setsuko; Murai, Yuta; Monde, Kenji; Hirano, Ken-ichi; Jin, Takashi
Abstract : A near infrared fluorescence labelled long-chain fatty acid (FFA), Alexa680-BMPP (BMPP: 15-(4-(3-aminopropyl)phenyl)-3-methyl pentadecanoic acid), was synthesized as a fluorescent probe toward optical imaging of cardiac metabolism. Abstract : Non-invasive fatty acid (FA) metabolic imaging is crucial for the evaluation of cardiac function in the heart. Currently, single-photon emission computed tomography (SPECT) and positron emission tomography (PET) are widely employed for cardiac metabolic imaging both in pre-clinical and clinical studies. Although SPECT and PET enable highly sensitive cardiac metabolic imaging, there are several disadvantages such as the high cost of instruments and radioactive tracer synthesis. In contrast, near-infrared (NIR) optical imaging using fluorescent FAs provides a simple and useful platform for in vivo imaging of cardiac metabolism. In this work, we synthesized a NIR fluorescence labelled long-chain fatty acid (LCFA) for real-time imaging of cardiac metabolism in vivo . A NIR fluorescence labelled LCFA was designed as an analogue of β-methyl [ 123 I] iodophenyl-pentanedecanoic acid ( 123 I-BMIPP), which is widely used for the diagnosis of heart diseases in clinical practice. As a NIR fluorescent label, we used an Alexa 680 fluorophore that emits over 700 nm. By conjugation of Alexa 680 to Amino-BMPP (15-(4-(3-aminopropyl)phenyl)-3-methylpentadecanoic acid), we prepared a NIR fluorescent BMIPP analogue, Alexa680-BMPP. NIR fluorescence imaging showed that Alexa680-BMPP is taken up by the mouse heart tissue after intravenous injection, showing that Alexa680-BMPP can act as a fluorescent LCFA analogue. Among Alexa680 conjugated FA analogues including short and middle chain NIR fluorescent FAs, Alexa680-BMPP was most efficiently taken up by heart tissues. For fasted and fed mice, the difference in the degree of the uptake of Alexa680-BMPP in their heart tissues was clearly observed by in vivo and ex vivo NIR fluorescence imaging. Herein, we present the synthesis of a NIR fluorescent LCFA, Alexa680-BMPP, and its capability for real-time optical imaging of cardiac metabolism in living mice.